Computational Investigation of Aditoprim and Brodimoprim as Green Corrosion Inhibitors: Integrating DFT, Topological Analyses, and Monte Carlo Simulations - Kareem, Rebaz Obaid; Azeez, Yousif Hussein; Omer, Rebaz Anwar; Ahmed, Lana Omer; Hekim, Seda (Pleiades Publishing Ltd, 2025)
Corrosion, the oxidative degradation of metals in aggressive environments, poses significant economic and environmental challenges. This study comprehensively evaluates the structural, electronic, and adsorption properties of Aditoprim (ADP) and Brodimoprim (BDP) as green corrosion inhibitors using density functional theory DFT and B3LYP/6-311++G(2d,p) level of theory, topological analyses, and Monte Carlo (MC) simulations in dry and acid environment comprising 100 water molecules, 4 hydronium ions (H3O+), and 4 chloride ions (Cl-1). A 25 & Aring; vacuum layer was applied along the *c*-axis to mitigate periodic interactions on the Fe(110) surface. Fukui function and Mulliken charge analyses identify nucleophilic/electrophilic sites, while MEP maps highlight reactive regions. Results reveal efficient electron charge transfer from inhibitor to metal, with ADP exhibiting superior adsorption energy and electron-donating ability, attributed to its dimethylamino moiety. The lower HOMO-LUMO energy gap of ADP (4.636 eV) compared to BDP (5.138 eV) correlates with higher reactivity and inhibition potential. These computational insights support the design of effective green corrosion inhibitors.
Keywords: aditoprim, Brodimoprim, DFT, Monte Carlo simulations, corrosion; Fe(110) metal surface